2012
DOI: 10.1002/j.1875-9114.2012.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Potential Opioid‐Related Adverse Effects and Hospital Length of Stay in Patients Receiving Opioids After Orthopedic Surgery

Abstract: Constipation, emesis, and confusion were associated with increased p-LOS in patients receiving opioids after orthopedic surgery. In addition, there was a significant linear relationship between the number of adverse effects/patient and increased p-LOS, and the strength of the association increased as the number of adverse effects increased. Although the opioid dosages and adverse-effect rates were typical, these findings reinforce the need to balance pain management with risk of events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 50 publications
4
82
1
4
Order By: Relevance
“…In one 2007 study, there was an increase of 7% and 10% in these parameters, respectively, in patients experiencing postsurgical ORAEs, compared with a matched control group who did not have ORAEs 10 . In a retrospective study of 402 patients undergoing orthopedic surgery, opioid-related AEs of constipation, confusion, and emesis were significantly associated with longer hospital stays (1.4, 1.1, and 0.7 additional days, respectively; p50.01 for all comparisons) compared with patients who did not experience these AEs 29 . Another analysis of data from nearly 320,000 inpatients who underwent colectomy, cholecystectomy, total abdominal hysterectomy, or hip replacement found that the group who experienced an ORAE (n ¼ 39,116) remained in the hospital an average of 3.3 days longer, and had average hospital costs that were about $4700 more than a control group without ORAEs (n ¼ 280,782) 30 .…”
Section: Discussionmentioning
confidence: 98%
“…In one 2007 study, there was an increase of 7% and 10% in these parameters, respectively, in patients experiencing postsurgical ORAEs, compared with a matched control group who did not have ORAEs 10 . In a retrospective study of 402 patients undergoing orthopedic surgery, opioid-related AEs of constipation, confusion, and emesis were significantly associated with longer hospital stays (1.4, 1.1, and 0.7 additional days, respectively; p50.01 for all comparisons) compared with patients who did not experience these AEs 29 . Another analysis of data from nearly 320,000 inpatients who underwent colectomy, cholecystectomy, total abdominal hysterectomy, or hip replacement found that the group who experienced an ORAE (n ¼ 39,116) remained in the hospital an average of 3.3 days longer, and had average hospital costs that were about $4700 more than a control group without ORAEs (n ¼ 280,782) 30 .…”
Section: Discussionmentioning
confidence: 98%
“…Less commonly, opioid monotherapy has been associated with ileus [16], respiratory depression [17], falls, and delirium, and in some extreme cases even death [18]. Numerous studies have demonstrated that managing these ORADEs is costly and they are associated with increased LOS [1922]. …”
Section: Introductionmentioning
confidence: 99%
“…Naloxone use for the treatment of opioid-induced respiratory depression was cited in 4.6% of all ADEs reported in one analysis. 7 Even with the availability of this antidote, opioid-induced adverse events can lead to increased costs of care due to an increased length of stay, 8 the need for additional medications, and lawsuits. 9 A study evaluating over 4000 patients admitted to two tertiary care hospitals found that the more seriAm J Health-Syst Pharm-Vol 71 May 1, 2014 ous ADEs were typically regarded as preventable.…”
mentioning
confidence: 99%